2016
DOI: 10.17586/2220-8054-2016-7-1-111-117
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, isolation, and X-ray structural characterization of trifluoromethylated C78 fullerenes: C78(2)(CF3)10/12 and C78(3)(CF3)12/14

Abstract: Four CF 3 derivatives of C 78 , C 78 (2)(CF 3 ) 10/12 and C 78 (3)(CF 3 ) 12/14 , have been isolated via HPLC from the products of high-temperature trifluoromethylation of a C 76 -C 96 fullerene mixture or a C 78 fraction. Their molecular structures were determined by single crystal X-ray crystallography using synchrotron radiation. The addition patterns of the new compounds are compared with each other and with the previously known C 78 (2)(CF 3 ) 10 and C 78 (3)(CF 3 ) 12 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The involvement of all pentagons into fullerene derivatization was observed in most derivatives with 12 or more addends. However, some exceptions are known for chloro and CF 3 derivatives as a consequence of an enhanced stability of specific substructures formed on a fullerene cage . For instance, two pentagons are free from additions in the structure of C 88 (7)Cl 24 …”
Section: Figurementioning
confidence: 99%
“…The involvement of all pentagons into fullerene derivatization was observed in most derivatives with 12 or more addends. However, some exceptions are known for chloro and CF 3 derivatives as a consequence of an enhanced stability of specific substructures formed on a fullerene cage . For instance, two pentagons are free from additions in the structure of C 88 (7)Cl 24 …”
Section: Figurementioning
confidence: 99%
“…Chloro and bromo derivatives are known for C 78 (1)Cl 30 , C 78 (2,3)Br 18 , C 78 (2,3,5)Cl 18 ,, and C 78 (2)Cl 30 . For the same four IPR isomers, perfluoroalkyl derivatives were isolated and structurally characterized by either X‐ray crystallography or 19 F NMR spectroscopy for C 78 (1)(CF 3 ) 10 , C 78 (2)(CF 3 ) 10,12 , C 78 (2)(C 2 F 5 ) 10 , C 78 (3)(CF 3 ) 8,12,14 , and C 78 (5)(CF 3 ) 12 . Therefore, among others, CF 3 derivatives of isomer C 78 (1) belong to the less investigated and structurally characterized compounds.…”
Section: Figurementioning
confidence: 99%
“…An X‐ray diffraction study with the use of synchrotron radiation revealed the known structure of C 78 (1)(CF 3 ) 10 (toluene solvate) and fourteen new structures of C 78 (1)(CF 3 ) 10−18 (see Table S1 in the Supporting Information). The structures of the isolated CF 3 derivatives of isomers C 78 (2) and C 78 (3) have been presented in a separate publication …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation